Pengenalan Budidaya Sayuran Hidroponik dan Pembuatan Pupuk Organik Fermentasi pada Kelompok Tani di Kecamatan Pelaihari - Riza Adrianoor Saputra; Jumar Jumar; Noor Laila Aziza; Untung Santoso; Muhammad Imam Nugraha; Komala Aminda Putri (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2021)
Agricultural technology with a hydroponic system is an alternative in the use of narrow land to increase the availability of vegetables to be fulfilled in Pelaihari Sub-District, Tanah Laut Regency. Most of the land in Pelaihari District has a low level of fertility and the lack of knowledge of farmers in increasing soil fertility. Therefore, efforts to increase soil fertility are needed through counseling and training in the manufacture of fermented organic fertilizers made from agricultural waste, it is hoped that fertility will increase and agricultural waste can be utilized. This activities uses lecture methods, discussions and direct practice in the field based on the results of initial observations as the basis for determining the level of understanding and insight of farmers.  Before the extension activities were carried out, a list of questions (questionnaires) was distributed and after the activity was completed, this list of questions was distributed again. Community service activities in the form of counseling and training on hydroponic system vegetable cultivation and the manufacture of fermented organic fertilizers. Based on the results of the pre-instruction and post-training questionnaires, it was found that an increase in the knowledge of activity participants was 12.73%. The hydroponic system used in this community service is a wick system and also a technique for making fermented organic fertilizer (bokashi) made from agricultural waste and livestock waste.